Enriching Doctoral-Level Preparation Programs through a Nationwide Consortium Model: The National Leadership Consortium in Sensory Disabilities. (November 2017) - Kruemmling, Brooke; Hayes, Heather; Smith, Derrick W.
The National Leadership Consortium in Sensory Disabilities (NLCSD) trained doctoral scholars at universities across the United States to increase the number and quality of professionals specializing in educating children with sensory disabilities. NLCSD produced 40 new doctorates and created a community of learners comprised of scholars, faculty, and leaders in policy and advocacy.